Homoeologous exchange enables rapid evolution of tolerance to salinity and hyper-osmotic stresses in a synthetic allotetraploid wheat. (3rd September 2022) - Wang, Bin; Lv, Ruili; Zhang, Zhibin; Yang, Chunwu; Xun, Hongwei; Liu, Bao; Gong, Lei
Abstract: The link between polyploidy and enhanced adaptation to environmental stresses could be a result of polyploidy itself harbouring higher tolerance to adverse conditions, or polyploidy possessing higher evolvability than diploids under stress conditions. Natural polyploids are inherently unsuitable to disentangle these two possibilities. Using selfed progenies of a synthetic allotetraploid wheat AT3 (AADD) along with its diploid parents, Triticum urartu TMU38 (AA) and Aegilops tauschii TQ27 (DD), we addressed the foregoing issue under abiotic salinity and hyper-osmotic (drought-like) stress. Under short duration of both stresses, euploid plants of AT3 showed intermediate tolerance of diploid parents; under life-long duration of both stresses, tolerant individuals to either stress emerged from selfed progenies of AT3, but not from comparable-sized diploid parent populations. Tolerance to both stresses were conditioned by the same two homoeologous exchanges (HEs; 2DS/2AS and 3DL/3AL), and at least one HE needed to be at the homozygous state. Transcriptomic analyses revealed that hyper-up-regulation of within-HE stress responsive genes of the A sub-genome origin is likely responsible for the dual-stress tolerant phenotypes. Our results suggest that HE-mediated inter-sub-genome rearrangements can be an important mechanism leading to adaptive evolution in allopolyploids as well as a promising target for genetic manipulation in crop improvement. Abstract : Homoeologous exchange-mediated inter-sub-genome rearrangements can be an important mechanism leading to adaptive evolution in allopolyploids, as well as a promising target for genetic manipulation in crop improvement.